Design of electrical installation data information system using fdd method (case study PT. PLN Persero) - Ryan Rivaldi; Nofita Rismawati; Rayung Wulan (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
This study aims to build a system that can assist in data processing in order to make it easier for employees to do their work to reduce errors so that there is no duplicate data or data loss, facilitate access to customer data that is needed by officers so that the flow of information can be received more quickly, especially in electrical installation services. The research method used is qualitative research methods with data processing systems, namely data collection techniques such as interviews, observations made at PT. PLN Persero Depok II. This research system development model uses the BlackBox Testing method. Based on the results of the research conducted, the author can conclude that the existing system in the company still uses a ledger so that it is very vulnerable to data loss, so with the Java-based electrical installation service application that has been designed by the author, every data processing will be computerized and make it easier in every process. search for data and reports quickly and accurately which will later be submitted to the head of the company PT. PLN Persero Depok II.